Mortality of fish escaping trawl gears - Suuronen, Petri (FAO RomeIT, 2005)
Assesses and summarizes the principal factors affecting the stress, injury and mortality of fish that arise fom fishing processes, particularly when fish escape from trawl gears. Attempts to evaluate the key principles for designing fishing gears and operations that reduce or eliminate the mortality of escapees. Assesses the problem associated with estimating the impacts of unaccounted fish mortality.